PENYULUHAN PENGOLAHAN MAKANAN BERGIZI BAGI MAHASISWA INDEKOS SEBAGAI UPAYA PENCEGAHAN KECANDUAN MIE INSTAN - Devi Eliza; Yoyoh Jubaedah; Nenden Rani Rinekasari (LPPM Universitas Al Muslim, 2023)
A lot of busyness in various activities makes a person not prioritizing their basic needs, such as food, especially students who live in boarding houses, whom can even consume several types of instant noodle food in a single day. Consuming instant noodles in large quantities and for a long time causes the accumulation of addictive substances contained in instant food in the body. Thus, many students suffer from stomach ulcers, inflammation and various diseases that attack the digestive system. Counseling about the processing of nutritious food was carried out to a student at the Indonesian University of Education who was happen to be a neighbor of the activity instructor's boarding house. One way to reduce instant noodles is to cook it yourself. The counseling approach used was in the form of eclectic counseling, which was a combination of directive counseling and non-directive counseling approaches. The results of counseling showed that clients can carry out counseling activities well and can apply cooking activities in their daily lives, so they can reduce consuming instant noodles. Therefore, it is hoped that similar activities can be carried out by clients continuously so that clients can reduce consuming instant noodles